Wake Forest students painting banner - Talley, Lisa (Z. Smith Reynolds Library, 1970)
nd
Female students spray-painting banner
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth